Essential Integration of eHRM 4.0 Approach, IT Infrastructure and CEO Support to Support Supply Chain Performance in Small-Scale Logistics Companies - Mashudi; Fauziah, Luluk; Kurniawati, Nurul Imani (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: IT infrastructure resources in large-sized companies have evolved into large-scale intelligent enterprise systems due to the emergence of Big Data, Internet of Things, and artificial intelligence technologies.OBJECTIVES: The purpose of this study was to analyze the effect of eHRM implementation and the availability of IT infrastructure on top management/CEO support and the performance of logistics companies in Semarang city. METHODS: This study uses a quantitative method with an analytical tool using SEM-PLS. The sampling method for this study used a purposive sampling technique with a total sample of 120 samples. RESULTS: IT infrastructure has a significant effect on top management support in logistics companies, the role of eHRM has a significant effect on top management support, the role of eHRM has a significant effect on CEO support, eHRM has a significant effect on company performance, IT infrastructure has a significant effect on company performance, support CEO has a significant effect on company performance, IT infrastructure has a significant effect on company performance, and the role of eHRM has no significant effect on company performance.CONCLUSION: IT Infrastructure and CEO Support influence Supply Chain Performance in Small-Scale Logistics Companies.
Keywords: eHRM; IT Infrastructure; CEO Support; Company Performance; Logistics Company